CROSSING THE DEMOGRAPHIC RIFT: A STUDY OF EMPLOYEE ENGAGEMENT AND RETENTION IN BANKS OF HARYANA - Rani, Kanchan; Kaur, Ramandeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study explores the impact of demographic variables on employee engagement and retention in Haryana (India) banking industry. The study is based on the sample of 400 employees from public and private operational banks in five prominent cities, using stratified random sampling technique to maintain the representation of different job levels and demography. Independent t-tests and ANOVA were employed to examine differences in engagement and retention by gender, marital status, age, and education level. The findings indicated statistically significant differences; that is, male employee had higher engagement, and female teachers had higher retention. Age and qualification variables also demonstrated significant effects for engagement and retention with 41-50 age group and post-graduates with the highest levels of engagement. Retention was affected by marital status, with married employees more likely to sustain their organizations. Findings emphasise the necessity for HR managers to create custom solutions, considering demographic differences in designing engagement and retention initiatives. It also highlights the possible benefits to the organization of more inclusive and focused HR practices. The results add to the overall knowledge on demographic effects on work behaviour in the Indian banking sector and provide a springboard for further research and policy interventions.